Effect of support on the performance of PtRu-based catalysts in oxidative steam reforming of ethanol to produce hydrogen - Tang, Chih-Wei; Liu, Chiu-Hung; Yu, Shen-Wei; Wang, Chen-Bin (Frontiers in Chemistry, 2022)
Oxidative steam reforming of ethanol (OSRE) to produce hydrogen has been investigated over a series of supported PtRu catalysts, with different supports. Bimetallic PtRu-based catalysts were prepared by method of impregnation by using H2PtCl6 and RuCl3 as precursors. Six supports (reducible oxides of ZrO2, CeO2, Co3O4 and irreducible oxides of ZnO, Al2O3, NiO) were chosen to fabricate bimetallic catalysts. The catalytic performance of series PtRu-based samples regarding the OSRE reaction was evaluated with a fixed-bed flow reactor under atmospheric pressure. In front reaction, the catalyst was pre-activated by reduction under 200 C for 3 h. The gas hourly space velocity was adjusted at 66,000 h-1, the optimal molar ratios of H2O/EtOH and O2/EtOH feeds were 4.9 and 0.44, respectively. The results indicated that the PtRu supported on ZrO2 and CeO2 exhibited superior catalytic performance in OSRE reaction under low temperature (TR approximately 320 C) for producing the main products of H2 and CO2 with lower CO and CH4 by-products. Also, it is quite stable during a long time evaluation, i.e. the maximum YH2 maintains 4.4  4.2 and the CO distribution approaches 3.3  3.5 mol % around 84 h test at 340 C over the PtRu/ZrO2 catalyst.